Conflicting perspectives during guidelines development are an important source of implementation failure. (May 2023) - Michaels, Jonathan A; Maheswaran, Ravi
Highlights: Evidence-based guidelines are not value-free but require trade-offs between multiple desirable objectives. National guidance may reflect the specific perspective of the agency developing it. Recommendations frequently address societal objectives, such as cost effectiveness, equity, and innovation. This may conflict with patients' preferences, and desire to maximise clinical effectiveness. Such conflicting perspectives have important implications for guidance development, dissemination, and implementation. Abstract: In recent years many countries have created national bodies that provide evidence-based guidance and policy relating to the commissioning and provision of healthcare services. However, such guidance often fails to be consistently implemented. The differing perspectives from which guidance is developed is suggested as a significant contributor to these failures. A societal perspective is, necessarily, taken by policy makers, while patients and their healthcare professionals are primarily concerned with an individual perspective. This is particularly likely to impair implementation where national policy objectives, such as cost effectiveness, equity, or the promotion of innovation, are embodied in the guidance, while patients and healthcare professionals may consider it appropriate to over-ride these, based upon individual circumstances and preferences. This paper examines these conflicts with reference to guidance issued by the National Institute of Health and Care Excellence in England. Conflicts are identified between the objectives, values, and preferences of those who develop and those who implement such guidance, with consequent difficulties in providing helpful personalised recommendations. The implications of this for the development and implementation of guidance are discussed and recommendations are made regarding the ways in which such guidance is framed and disseminated.